2021
DOI: 10.3389/fnhum.2021.660948
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationship Between Speech Perception, Production Distinctness, and Production Variability

Abstract: Several studies have demonstrated that individuals’ ability to perceive a speech sound contrast is related to the production of that contrast in their native language. The theoretical account for this relationship is that speech perception and production have a shared multimodal representation in relevant sensory spaces (e.g., auditory and somatosensory domains). This gives rise to a prediction that individuals with more narrowly defined targets will produce greater separation between contrasting sounds, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The American English vowel was analysed in terms of production and perception. The authors have found participants in a group of high-vision skills to produce a vowel with a greater degree of comparison [17]. Some tend to support theoretical predictions and evaluating formant frequency in human identity.…”
Section: Related Workmentioning
confidence: 66%
“…The American English vowel was analysed in terms of production and perception. The authors have found participants in a group of high-vision skills to produce a vowel with a greater degree of comparison [17]. Some tend to support theoretical predictions and evaluating formant frequency in human identity.…”
Section: Related Workmentioning
confidence: 66%
“…In the context of this model, the sensorimotor interface provides two potential mechanisms for vocal control: First, an internal mechanism in which forward predictions are checked against their sensory targets allowing for error correction prior to and shortly after the onset of utterance when the actual auditory feedback has not yet become available ( Hickok, 2012 ); and second, an external mechanism in which sensory representations of vocal output are compared against the actual auditory feedback for error detection and motor correction. Evidence from previous studies has supported the notion of an internal control mechanism by showing that neurotypical speakers rapidly (i.e., within ~50 ms) move their peripheral productions toward the center of their vowel space in the absence of any external feedback alterations, and this effect is associated with reduced motor-induced suppression of neural activities compared with production trials that closely match sensory targets near the center of the intended vowel sounds ( Cheng et al, 2021 ; Niziolek et al, 2013 ). In the present study, we found that when speakers with aphasia produced vowel sounds under normal feedback, damage to left-hemispheric frontal networks involving the inferior frontal pars orbitalis and precentral gyri predicted the impairment of vocal feedback control in the earlier phases of neural processing as indexed by the aberrant modulation of short-latency N1a ERP responses at 0 – 50 ms following vocalization onset.…”
Section: Discussionmentioning
confidence: 84%
“…For example, Kaewchum (2018) showed that the link between the overall perception and production of the investigated consonants was generally weak positive. He also found that the correlations between the production and perception of /p/, /k/, /g/, /f/, /v/, /s/, /z/, and /ʃ/ were very weak positive; however, between producing and perceiving /t/, it was weakly positive; while, between the /l/ production and perception, it was weakly negative (see also Sakai & Moorman, 2018;Sioson & Chang, 2017;Zhang et al, 2021) Nevertheless, other studies proved no correlation between the perception and production of English vowels (e.g., Cheng et al, 2021;Zhang et al, 2016) or consonants (e.g., Huensch, 2013;Pei, 2022;Seo & Lim, 2016) by EFL/ESL listeners. For example, Seo and Lim (2016) found that those with lower English proficiency exhibited greater accuracy in production than perception, denoting no link between the two modalities.…”
Section: The Correlation Between the Production And Perception Of Eng...mentioning
confidence: 98%
“…Despite the SLM and PAM's claimed link between speech production and perception, empirical evidence for such a link is not consistent (Schmitz et al, 2018) and is still unclear (Baese-Berk, 2019). Some past studies examined the connection between the two capacities in L2 learning, revealing a variety of outcomes from strong relationships (e.g., Chao et al, 2019;Syed, 2011) to moderate (e.g., Berti et al, 2020;Hattori, 2010), weak (e.g., Kaewchum, 2018Sioson & Chang, 2017), or no link between these two modalities (e.g., Cheng et al, 2021;Zhang et al, 2016). Chao et al (2019) aimed to investigate the link between vowel perception and vowel production variability.…”
Section: The Correlation Between the Production And Perception Of Eng...mentioning
confidence: 99%